Understanding health anxiety in the COVID-19 pandemic. (December 2022) - Heinen, Anna; Varghese, Sherin; Krayem, Amani; Molodynski, Andrew
Background: The COVID-19 pandemic continues to be one of the greatest public health challenges faced by the UK. Reported rates of psychiatric difficulties have increased and the mechanisms by which the pandemic has affected mental health requires investigation. Aims: The aim of the study was to understand the psychological impact of the COVID-19 pandemic on health anxiety in the general population, with a focus on Oxford Health NHS Foundation Trust, which provides specialist mental health care within Oxfordshire and Buckinghamshire. Methods: We invited participants aged 18+ across Oxfordshire and Buckinghamshire to complete an online questionnaire consisting of standardised questionnaires measuring psychological wellbeing, non-standardised questions to provide demographic information, and information about social circumstances and behaviour during the COVID-19 pandemic. Participants were then invited via email to complete a 3-month follow-up questionnaire. Results: About 324 participants completed the baseline survey while 199 completed the follow-up. Our analysis demonstrated that higher scores on a health anxiety inventory were related to reports of depression, anxiety, loneliness, poor quality of life and obsessive-compulsive symptoms and panic. We also identified several predictors of health anxiety such as being female, having a pre-existing physical or mental health condition, and poor tolerance of uncertainty. Lifestyle and demographic factors such as changes in financial situation, changes in employment status, having a close relative or friend with COVID-19, being able to do grocery shopping, being a key worker, and ethnicity were not found to predict health anxiety. Conclusions: Awareness of the impact of health anxiety on people needs to be consistently high among healthcare professionals, especially in the continuing fallout from the COVID-19 pandemic. The relationship between health anxiety and fatigue, sleep quality, gender and co-morbid mental and physical health difficulties needs to be investigated further to determine areas of intervention.